Effect of a Combination of Photodynamic Therapy and Chitosan on Streptococcus mutans (An In Vitro Study) - Mirfasihi, Armin; Malekafzali, Beheshteh; Ebrahimi zadeh, Hosna; Sanjari, Khashayar; Mir, Maziar (Journal of Lasers in Medical Sciences, 2020)
Introduction: This study aimed to assess the effect of photodynamic therapy (PDT) and chitosan separately and in combination with Streptococcus mutans. Materials and Methods: This in vitro experimental study evaluated 216 microbial samples in 6 groups. First, 5 μL of 0.5 McFarland standard suspension of S. mutans was added to each well of an ELISA microplate; 100 μL of Mueller Hinton broth was also added to each well; 180 wells contained S. mutans suspension while 36 wells were devoid of bacteria. Group 1 served as the negative control and had no bacteria. Group 2 served as the positive control and S. mutans in the positive control wells did not undergo any intervention. In groups 3 and 4, PDT with a 50 mW low-level laser was performed for 30 and 40 seconds respectively. In group 5, 3 mg/mL of chitosan (100 μL) was used. In group 6, 3 mg/mL (100 μL) of chitosan was used in combination with PDT (50 mW laser for 30 seconds). The laser was irradiated under aseptic conditions at a 660 nm wavelength with 50 mW power. Data were analyzed using one-way ANOVA and Tukey’s test. Results: PDT combined with chitosan showed maximum bactericidal effect followed by PDT for 40 seconds and chitosan groups (P < 0.05). PDT for 30 seconds showed a minimum bactericidal effect (P < 0.05). All pairwise comparisons revealed significant differences (P < 0.001). Conclusion: Chitosan and PDT alone can be used to decrease the S. mutans count. However, their combined use has a greater bactericidal effect on S. mutans.